Is there a link between deep‐sea biodiversity and ecosystem function?. (18th April 2013) - Leduc, Daniel; Rowden, Ashley A.; Pilditch, Conrad A.; Maas, Elizabeth W.; Probert, P. Keith
Abstract Studying the diversity‐ecosystem function relationship in the deep sea is of primary importance in the face of biodiversity loss and for our understanding of how the deep sea functions. Results from the first study of diversity‐ecosystem function relationships in the deep sea (Danovaro et al. 2008; Current Biology, 18, 1–8) are unexpected and show an exponential relationship between deep‐sea nematode diversity and ecosystem function and efficiency, although this relationship appears largely restricted to relatively low diversities [ES(51) <25]. Here, we investigate the relationship between nematode diversity and several independent measures/proxies of ecosystem function (sediment community oxygen consumption, bacterial biomass, bacterial extracellular enzyme activity) and efficiency (ratio of bacterial/nematode carbon to organic C content of the sediment) on the New Zealand continental slope. Nematode diversity at our study sites was relatively high [ES(51) = 30–42], and there was no relationship between species/functional diversity and ecosystem function/efficiency after accounting for the effects of water depth and food availability. Our results are consistent with a breakdown of the exponential diversity‐function relationship at high levels of diversity, which may be due to increased competition or greater functional redundancy. Future studies need to take into account as many environmental factors and as wide a range of diversities as possible to provide further insights into the diversity‐ecosystem function relationship in the largest ecosystem on Earth.